Implementasi Metode Eksperimen Membuat Es Krim Untuk Meningkatkan Hasil Belajar IPA Peserta Didik Kelas VII - Ariani, Veggy; Kariadinata, Rahayu; Minan Chusni, Muhammad (CAHAYA: Journal of Research on Science Education, 2025)
The purpose of this study is to find out the effectiveness of the experimental method of making ice cream on the material of changing the form of substances on improving the learning outcomes of science students in grade VII at SMP Negeri 1 Sukaluyu. This study uses a quantitative approach with a One Group Pretest Posttest design. The subjects of this study are class VII students with a total of 35 people. The instruments used are tests of student learning outcomes in the form of pretest and posttest. This data was analyzed with the Shapiro Wilk  Test to test the normality of data distribution. The test differs by using a paired simples-test to test whether there is an average difference between two paired samples. The results of the analysis showed that the average score of the posttest was higher than the average score of the pretest. Pretest and posttest data are normal with significance in the pretest of 0.646 and posttest of 0.270. The statistical test showed a Sig. (2-tailed) value < 0.05, which means that there was a significant difference between the learning outcomes before and after the application of the experimental method. The N-gain obtained is 63,30 with a medium category so that it can be said to be quite effective.